Restless planet - Keach, Stacy; Carroll, Michael (Narrator).; Keller, Mark.; Coyote, Peter; National Geographic Society (U.S.).; National Geographic Television ([Washington, D.C.] National Geographic Society, 2011)
"Experience the devastating power of explosive volcanoes, ground-buckling earthquakes, deadly tornadoes, hurricanes and tsunamis as National Geographic heads into the field with scientists who risk their lives to study these fearsome natural phenomena. Featuring over five hours of programming, Restless planet captures extraordinary scenes of destruction from the air, the ground and from inside a tornado and the moving, human side of the story from tales of heroism and tragedy to dedicated teams of experts racing to understand and ultimately better predict the deadly forces of nature."--Container.
disc 1. Volcano : nature's inferno (1997 ; full screen) ; narrated by Stacy Keach ; produced by Gail Willumsen, Teresa Koenig ; written by Gail Willumsen ; music, Jay Chattaway ; editor, Yaffa Lerea -- disc 2. Tsunami : killer wave (1997 ; full screen) ; producer, Kevin Bachar ; writer, Jaime Bernanke ; cinematographer, Paul Atkins ; narrator, Michael Carroll -- disc 3. Tornado intercept (2005 ; widescreen) ; producer/writer, Lawrence Cumbo ; editor, Emmanuel Mairesse ; narrator, Mark Keller -- disc 4. Nature's fury (2000 ; full screen) ; writer/producer, Jaime Bernanke ; editor, Jud Johnston ; music, Richard Fiocca -- disc 5. Storm of the century (1998 ; full screen) ; narrator, Peter Coyote ; produced by Barry D. Nye ; editor, Cory Taylor ; written by Kevin McCarey ; music, Mark Adler.
Title from container
In container
Originally produced between 1997 and 2005 and shown on National Geographic Television
"Presented in a format preserving the aspect ratio of its original television exhibition"--Container
Special features: disc 1. Into the volcano & photo gallery; disc 3 bonus program: Into the tornado; disc 4 bonus program :Tornado hunters", "Lightning strikes"; photo gallery; U.S. natural disaster map; geographica quiz; other programs from National Geographic.
Keywords: Natural Disasters; Volcanoes; Tsunamis; Tornadoes; Storm Chasers; Earthquakes; Hurricanes